ORIENTATION OF STUDENTS TO INNOVATIVE CREATIVITY IN AN INNOVATIVE EDUCATIONAL ENVIRONMENT - To‘xtayeva Zebo Sharifovna; Rahmatova Barnogul Karimjonovna (Journals Park Publishing, 2024)
This article analyzes the innovative activities of the education system in the context of economic, socio, political and cultural changes in society, creates innovative environment of educational institutions, stimulates creativity among students and develops their independent thinking skills. The article discusses the methods of interactive teaching, the use of modern technologies, project-based teaching and creative thinking training, as well as the importance of problem solving, assessment of creativity and the importance of innovation in the educational process, the organization of innovative learning environment in the formation of students as creative individuals.
Keywords: innovative education, educational institutions, creativity, students, interactive learning, modern technologies, project-based learning, creative thinking, problem solving, creativity assessment, independent thinking, learning process, intellectual.